Critical concepts for the creative humanities - Tuin, Iris van der; Verhoeff, Nanna (Lanham, Maryland Rowman & Littlefield, 2022)
"Critical Concepts for the Creative Humanities is the first book to outline and define the specific and evolving field of the creative humanities and provides the field's nascent bibliography"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Creation (Literary, artistic, etc.) -- Encyclopedias; Arts -- Encyclopedias